Deciphering the Spatial Arrangement of Metals and Correlation to Reactivity in Multivariate Metal-Organic Frameworks. - Qi Liu; Hengjiang Cong; Hexiang Deng (Journal of the American Chemical Society, 2016)
Thirty-six porphyrin-based metal–organic frameworks (MOFs) with composition of (MO)(TCPP-M) and MO trigonal SBUs of various metals, MgO, MnO, CoO, NiO, and FeO including mixed-metal SBUs, MnFeO, NiFeO, CoNiO, MnCoO, MnMgO, and MnNiO were synthesized and characterized. These multivariate MOFs (MTV-MOFs) were examined by X-ray photoelectron spectroscopy, UV–vis diffuse reflectance spectra, and for the first time, their metal spatial arrangement deciphered and were found to exist in the form of either domains or well-mixed. We find that MTV-MOFs with well-mixed metals in their SBUs, rather than the SBUs having one kind of metal but different from one SBU to another, perform better than the sum of their parts in the test reaction involving the photo-oxidation of 1,5-dihydroxynaphthalene.